2004
DOI: 10.1038/nsmb848
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic response of upstream DNA to transcription-generated torsional stress

Abstract: The torsional stress caused by counter-rotation of the transcription machinery and template generates supercoils in a closed topological domain, but has been presumed to be too short-lived to be significant in an open domain. This report shows that transcribing RNA polymerases dynamically sustain sufficient torsion to perturb DNA structure even on linear templates. Assays to capture and measure transcriptionally generated torque and to trap short-lived perturbations in DNA structure and conformation showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
177
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 150 publications
(183 citation statements)
references
References 44 publications
4
177
1
Order By: Relevance
“…As the FUSE first melts in response to the torque generated by ongoing transcription (Figure 10, A and B), 5,12,13 FBP sequence selectively engages DNA via its KH motifs. 2,3,15,22 Then FBP loops and stimulates the p89/ XPB/ERCC3 3 0 to 5 0 helicase/translocase of TFIIH at the promoter increasing transcription.…”
Section: Discussionmentioning
confidence: 99%
“…As the FUSE first melts in response to the torque generated by ongoing transcription (Figure 10, A and B), 5,12,13 FBP sequence selectively engages DNA via its KH motifs. 2,3,15,22 Then FBP loops and stimulates the p89/ XPB/ERCC3 3 0 to 5 0 helicase/translocase of TFIIH at the promoter increasing transcription.…”
Section: Discussionmentioning
confidence: 99%
“…45 The torque generated by two divergently elongating RNAPII molecules can create sufficient supercoiling density in the chromatin between the two promoters to enable transition to non-B-DNA in vivo (reviewed in refs. [46][47][48]. Negative supercoiling is known to increase RNAPII transcription efficiency, and studies in vitro have shown that TFIIH can be dispensable for transcription initiation when there is sufficient negative supercoiling to assist in strand separation.…”
Section: Divergent Transcription and Negative Superhelical Tensionmentioning
confidence: 99%
“…In addition, when the stress is high enough, it can be released as strain in a variety of DNA structural transition: from B-DNA to Z-DNAs, cruciforms, quadruplexes, etc. [15][16][17][18] Proper gene expression occurs largely through the regulation of RNA polymerase transcription which arises at multiple stages: nucleosome remodeling and promoter selection, early transcription from the melting of DNA by the transcriptional machinery through the release of RNA polymerase from promoterproximal pause sites, transcript elongation, promoter-enhancer interaction, 3-D genomic architecture, and antisense activity. [19][20][21][22][23][24][25] Although there are no steps purely managed by DNA topology, a growing body of evidence indicates that DNA topology is an important player in the biochemical team.…”
Section: Introductionmentioning
confidence: 99%